Changes in Saliva Rheological Properties and Mucin Glycosylation in Dry Mouth. (December 2015) - Chaudhury, N.M.A.; Shirlaw, P.; Pramanik, R.; Carpenter, G.H.; Proctor, G.B.
Saliva is vital for the maintenance of normal oral physiology and mucosal health. The loss of salivary function can have far-reaching consequences, as observed with dry mouth, which is associated with increased orodental disease, speech impairment, dysphagia, and a significant negative effect on quality of life. The timely diagnosis of oral dryness is vital for the management of orodental disease and any associated often-undiagnosed systemic disease (e.g., Sjögren syndrome). Our aim was to investigate differences in mucin glycoproteins and saliva rheological properties between sufferers and nonsufferers of dry mouth in order to understand the relationship between saliva composition, rheological properties, and dryness perception and provide additional potential diagnostic markers. All patients exhibited objective and subjective oral dryness, irrespective of etiology. Over half of the patients ( n = 20, 58.8%) had a saliva secretion rate above the gland dysfunction cutoff of 0.1 mL/min. Mucin (MUC5B and MUC7) concentrations were generally similar or higher in patients. Despite the abundance of these moisture-retaining proteins, patients exhibited reduced mucosal hydration (wetness) and significantly lower saliva spinnbarkeit (stringiness), suggesting a loss of the lubricating and retention/adhesion properties of saliva, which, at least partially, are associated with mucin glycoproteins. Over 90% of patients with dry mouth (DMPs) consistently had unstimulated whole mouth saliva (UWMS) spinnbarkeit below the proposed normal cutoff (10 mm). Further analysis of mucins revealed the reduced glycosylation of mucins in DMPs compared to healthy controls. Our data indicate that UWMS mucin concentrations are not reduced in dry mouth but that the mucin structure (glycosylation) is altered. UWMS from DMPs had reduced spinnbarkeit, the assessment of which, in conjunction with sialometry, could improve sensitivity for the diagnosis of dry mouth. Additionally, it may be useful to take into consideration the altered mucin glycosylation and saliva rheological properties when designing synthetic or purified mucins for saliva substitutes and dry mouth therapy.